Unravelling the Profit Puzzle: How Chief Executive Officer Attributes Shape the Performance Sustainability of Nigerian Listed Firms - Wisdom, Okere; Cosmas, Ambe; Oladotun, Mabinuori; Akande, Bello Bashiru; Emmanuel, Ajayi Olusuyi; Lawrence, Imeokparia; Patrick, Ologbenla; Mathias, Opele Adedayo (International Review of Management and Marketing, 2025)
This study examined the impact of Chief Executive Officers’ attributes (age, gender and nationality) and performance sustainability (ROA, NPM) of listed firms in Nigeria. Secondary data was collated from listed firms in Nigeria’s stock market from 2014 to 2023. The variables were subjected to diagnostic tests and descriptive tests and the research objective was achieved using panel ordinary least square regression. The results revealed that CEO attributes (age, gender, nationality and board size) significantly affect the performance of quoted firms in Nigeria. The study findings call for effective governance, strategic leadership practices as well as tailored management policy formulation within the Nigerian business environment. This study offers practical insights into how Chief Executive Officers’ attributes can foster extended business success in emerging markets. These implications of the findings could further enlighten management decision-making and corporate governance as strategies to achieve sustainable performance in Nigeria either from revenue or profit perspective.